(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In contemporary society, educational systems are undergoing numerous changes, which in turn affects teaching approaches and methods. The application of new technologies, methods, and innovative teaching techniques leads to the creation of groundbreaking educational models that adapt to the needs of the time. This article explores the differences and similarities between traditional and modern educational approaches. Various aspects are discussed, including the use of information and communication technologies, the individualization of education, and the influence of globalization on educational processes. Key features that make modern education more flexible, accessible, and student-centered are highlighted.